Successful combination therapy of low-dose aspirin and unfractionated heparin in recurrent pregnancy loss: A case report - Adhi Pribadi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Habitual abortion, defined as more than two consecutive pregnancy losses, affects approximately 1% to 2% of women. This pathological condition undoubtfully frustrates a woman, yet this condition still has a chance to be treated and achieve a favorable pregnancy outcome. This case report aims to describe the success of a pregnancy with a history of recurrent miscarriages (five times of baby loss). The administration of a combination of low-dose aspirin and unfractionated heparin offers a 72-80% chance of having a good pregnancy outcome. We present a P2A5 woman with Thalassemia Minor and thrombocytosis. Preventive treatment, prenatal diagnosis, pregnancy outcomes, and complications were reviewed. Combination therapy of 80 mg aspirin and 2 x 5000 U unfractionated heparin subcutaneously during the last two pregnancies were able to maintain the pregnancy and prevent early pre-eclampsia or Fetal Growth Restriction (FGR) but not late-onset one. In the 6th pregnancy, the patient experienced late-onset FGR with a minor congenital anomaly. In the 7th pregnancy, severe pre-eclampsia appeared. However, administration of combination of heparin and aspirin could maintain pregnancy and fetal viability in Thalassemia Minor patients with recurrent abortus and thrombocytosis.